Between Divine Limits and Legal Reform: Muhammad Syahrur’s Ḥudūd Theory and the Reconstruction of Minimum Marriage Age in Indonesian Islamic Family Law - Arini Rufaida; Shofiyulloh (International Journal of Social Science and Religion (IJSSR), 2026)
This article examines the reform of the minimum marriage age in Indonesia through Muhammad Syahrur’s ḥudūd theory and its implications for contemporary Islamic legal epistemology. While previous studies have largely discussed Law No. 16 of 2019 from the perspectives of gender equality, child protection, and positive law, limited attention has been given to how this reform may be theoretically justified within a dynamic framework of Islamic legal reasoning. Using normative legal research, this study combines statutory, conceptual, and Islamic legal-theoretical approaches. It compares Law No. 1 of 1974 and Law No. 16 of 2019 and interprets the reform through Syahrur’s theory of limits, supported by relevant legal materials and scholarly literature. The study finds that raising and equalizing the minimum marriage age reflects not merely a legislative response to social problems, but also an epistemological shift in Islamic family law from rigid textualism toward contextual legal construction. Within Syahrur’s framework, the state’s determination of marriage age represents human ijtihād operating within divine boundaries, where legal norms may be adjusted to protect welfare, maturity, equality, and social justice. The article argues that the reform embodies an adaptive model of Islamic legal development that reconciles scriptural normativity with changing social realities. It contributes to debates on Islamic family law reform by showing that Syahrur’s ḥudūd theory offers a productive framework for legitimizing legal transformation without detaching Islamic law from its normative foundations.